Comprehensive Review of Big Data Analytics, Health Information Systems, And Data Privacy Ethics - Al Ahmadi, Muteb Salah Saad; Alhejaili, Fahad Mubarak; Alamry, Manal Sarhan; Aljhany, Amal Olyan; Al-Jahni, Munira Dakhil Allah; Albalawi, Manal Dhaher; algohani, Rehab abdalrahman; Almerashy, Hanaa Awaed Atheb; Alkhaibri, Turkiah Ghalaleb; Aljohani, Mousa Salem Awad (Journal of Ecohumanism, 2024)
The convergence of big data analytics and health information systems (HIS) has transformed the health care systems. It has so much potential to redesign and advance patient care and delivery processes and facilitate better decision-making. Nevertheless, using personal health data increases moral issues regarding personal data policy. This review aims to review the literature on handling big data analysis, health information systems, and data privacy ethics, focusing on existing trends, challenges, and prospects. This paper discusses the strengths of big data in healthcare delivery contexts, the growing function of health information systems, and the paramount role of ethical guidelines in addressing PWMI information. The review ends with proposing strategies to improve data privacy while at the same time optimizing the benefits of big data analytics in healthcare.